2023
DOI: 10.33395/sinkron.v8i1.11954
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Recommendation Systems in Determining Learning Strategies Using the Naïve Bayes Classifier Algorithm

Abstract: Recommendation systems are widely used in various fields of life to provide suggestions for a product, service, or piece of information to someone where there is an object to choose from. The recommendation system can also be applied in the field of education, especially in improving the quality of learning that occurs in schools. In this study, developing and implementing a recommendation system was used to determine the learning strategy applied in class. The system is very necessary in order to obtain effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…From the test results it can be concluded that there are 6 attributes that greatly influence the test, namely BTQ, Fiqh, Morals, Tauhid, Guardian and Active Service (Saleh et al, 2023). Comparison of the results of testing the Naïve Bayes Algorithm model without attribute selection with the Naïve Bayes Algorithm with Attribute Selection using Forward Selection is presented in the following table: Based on the results of testing with the Evaluation Confusion Matrix, it is proven that testing carried out using the Naïve Bayes algorithm optimization with Forward Selection has a higher accuracy score compared to using the Naïve Bayes algorithm without the selection feature.…”
Section: Discussion Naïve Bayes Algorithmmentioning
confidence: 99%
“…From the test results it can be concluded that there are 6 attributes that greatly influence the test, namely BTQ, Fiqh, Morals, Tauhid, Guardian and Active Service (Saleh et al, 2023). Comparison of the results of testing the Naïve Bayes Algorithm model without attribute selection with the Naïve Bayes Algorithm with Attribute Selection using Forward Selection is presented in the following table: Based on the results of testing with the Evaluation Confusion Matrix, it is proven that testing carried out using the Naïve Bayes algorithm optimization with Forward Selection has a higher accuracy score compared to using the Naïve Bayes algorithm without the selection feature.…”
Section: Discussion Naïve Bayes Algorithmmentioning
confidence: 99%
“…Additionally, Li & Rahman [11] proposed using a tree augmented Naive Bayes approach to detect students' www.ijacsa.thesai.org learning styles. Moreover, Saleh et al [12] implemented a recommendation system using the Naive Bayes classifier algorithm to determine learning strategies based on student learning styles with high accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Naive Bayes is easy to implement and requires a smaller amount of training data to estimate parameters, so it is effective for applications that require fast responses (Madjid, Ratnawati, & Rahayudi, 2023) (Anam, Rahmiati, Paradila, Mardainis, & Machdalena, 2023). Although simple, this method can be very effective if the assumption of independence between features is precise enough, and even if this assumption is violated, its performance is often still quite good (Lubis & Chandra, 2023) (Saleh, Dharshinni, Perangin-Angin, Azmi, & Sarif, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%